Intra-Industry Trade in High-Tech Product Groups within the South Korean Manufacturing Industry - Osman Barbaros Kemer; Muhammed Fatih Aydemir (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
The aim of this article is to determine the extent to which South Korea and other countries with which it has foreign trade relations are similar in terms of manufacturing industries producing high-tech products. To achieve this, the article analyses the intra-industry trade (IIT) of South Korea's manufacturing industry producing high-tech (high value-added) products. To this end, calculations were made using the Grubel-Lloyd index, which is the most widely used in the literature, with 3-digit (SITC-Rev.3) foreign trade data within the manufacturing sector for the period 2010-2022. With regard to South Korea's high-tech manufacturing industry and its foreign trade partners, it has been observed since 2010 that the IIT values in question exceed 0,57, with a value of 0,74 being reached in 2022. Conversely, while standard technology products played a significant role in achieving high IIT values in 2010, the increasing IIT values of high technology products since 2015 have been instrumental in South Korea's attainment of high IIT values. Furthermore, it has been established that this value is particularly concentrated in the machinery and transport sector and the chemical sector. It can thus be concluded that South Korea's foreign trade with other countries in the same or similar product groups is dominated by high-tech exports. Additionally, it has been observed that manufacturing industry products, which were previously included in inter-industry trade, have undergone a transformation towards IIT and have contributed to high IIT values. In order for South Korea to become a more prominent player in intra-industry trade in high-tech products, it is necessary for the country to implement more flexible production strategies and develop more comprehensive supply chains.